2010
DOI: 10.1111/j.1365-2672.2009.04581.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus-based evaluation of a virion concentration method and detection of enteric viruses in environmental samples by multiplex nested RT-PCR

Abstract: Aims:  The prevalence of enteric viruses in drinking and river water samples collected from Pune, India was assessed. During an outbreak of HEV in a small town near pune, water samples were screened for enteric viruses. Methods and Results:  The water samples were subjected to adsorption–elution‐based virus concentration protocol followed by multiplex nested PCR. Among 64 Mutha river samples, 49 (76·56%) were positive for Hepatitis A Virus, 36 (56·25%) were positive for Rotavirus, 33 (51·56%) were positive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The route of HEV transmission during outbreaks is well established, and was usually associated with the consumption of faecally contaminated drinking water [2,3,4,5,6,9,10,43,59]. In contrast, it is poorly documented for sporadic hepatitis E cases reported in both developing and developed countries [14,21,44,60].…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…The route of HEV transmission during outbreaks is well established, and was usually associated with the consumption of faecally contaminated drinking water [2,3,4,5,6,9,10,43,59]. In contrast, it is poorly documented for sporadic hepatitis E cases reported in both developing and developed countries [14,21,44,60].…”
Section: Epidemiologymentioning
confidence: 99%
“…Case-control studies have shown that consumption of boiled water significantly reduced the risk of epidemic HEV infection [6,59]. Strong arguments supporting the faecal-oral transmission of HEV during hepatitis E outbreaks came from recent studies conducted in India and Uganda [3,4,73]. Environmental investigations showed the presence of HEV RNA (of genotype 1) in river water samples collected during hepatitis E outbreaks in India [3,73], and the presence of HEV RNA in common hand washing water collected during the Kitgum District (Uganda) hepatitis E outbreak [4].…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations